A solution to Enhance VPN effect on wireless network Performance - Aswad, Subhi; Qasim, Muhanad (Nahrain University College of Engineering Journal, 2017)
This work presents a design of secured Wireless Network by utilizing Virtual Private Network (VPN) technique and provides a solution to enhance its performance by using Wireless Quality of Service technique (WQoS).A set of parameter are investigated include delay, throughput, jitter round trip time. These parameters are checked for a WLAN without VPN and WQoS, WLAN with VPN, and WLAN with VPN and WQoS.